2022
DOI: 10.1038/s43247-022-00597-1
|View full text |Cite
|
Sign up to set email alerts
|

Sources, sinks, and cycling of dissolved organic copper binding ligands in the ocean

Abstract: Organic Cu-binding ligands have a fundamental influence on Cu distributions in the global ocean and they complex >99% of the dissolved Cu in seawater. Cu-binding ligands however, represent a large diversity of compounds with distinct sources, sinks and chemical properties. This heterogeneity makes the organic Cu-binding ligand pool difficult to study at the global scale. In this review, we provide an overview of the diversity of compounds that compose the marine Cu-ligand pool, and their dominant sources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 244 publications
2
4
0
Order By: Relevance
“…At the same time, inputs from bottom sediments were limited. This may explain why deep waters did not present an increase in L Cu and dCu concentrations with depth, as observed in other oceans (Ruacho et al, 2022). Scavenging could remove more dCu than L Cu , as observed in the loss of linearity between the two parameters observed in the deep water (Figure 5B).…”
Section: Cu-binding Ligands In Deep Waterssupporting
confidence: 57%
See 2 more Smart Citations
“…At the same time, inputs from bottom sediments were limited. This may explain why deep waters did not present an increase in L Cu and dCu concentrations with depth, as observed in other oceans (Ruacho et al, 2022). Scavenging could remove more dCu than L Cu , as observed in the loss of linearity between the two parameters observed in the deep water (Figure 5B).…”
Section: Cu-binding Ligands In Deep Waterssupporting
confidence: 57%
“…This study found that the TPD was a substantial source of L Cu for the central Arctic surface waters (Tables 1, 2). Overall, the surface L Cu concentrations were higher than the average concentration for open ocean surface waters (~1 nM, Ruacho et al, 2022).…”
Section: Surface Water Distribution Of Cu-binding Ligandsmentioning
confidence: 77%
See 1 more Smart Citation
“…The contents of the oxidisable fractions of Pb and Cu (3–27% and 5–25%, respectively) may be due to the affinity of these metals for the organic matter that leads to the formation of complexes between them. Cu has tendency to form stable organo-Cu complexes due to its affinity towards humic substances, among other organic ligands [ 83 ]. The release of these elements is caused by the degradation of organic matter or oxidation of sulphides to sulphates under aerobic conditions [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Complexation of Cu by strong organic ligands is also a unique, and potentially important feature of marine Cu biogeochemistry (Ruacho et al., 2022). More than 99% of Cu in the surface ocean is bound by organic ligands (Buckley & van den Berg, 1986; Coale & Bruland, 1988), while free Cu (Cu 2+ ), which is the most bioavailable and toxic species, only accounts for a small portion of the dissolved Cu pool.…”
Section: Introductionmentioning
confidence: 99%